Circular economy of fashion: benefits and challenges for French micro and small brands - Dupont, Hadrien (Graduate School of Business (GSB), 2025)
The fashion industry is globally recognized as one of the major polluters, causing significant environmental and social concerns. Its complex value chain, from the intensive non-renewable resource use during raw material acquisition to human rights issues in manufacturing, and its unsustainable end-of-life solutions, underscores an industry struggling with profound challenges. In response to these challenges, the notion of a circular economy emerges as a transformative approach to reimagine and redesign production and consumption cycles, aiming to retain product value, reduce waste, and foster sustainability. The central research question of this study is the following: "What are the key challenges and opportunities for micro and small-sized fashion brands in adopting a successful circular business model?" Addressing this, the research provides a deep dive into the concept of circularity within the fashion sector, specifically focusing on French micro and small-sized brands. These brands, a blend of those organically born with sustainable principles and those that have adeptly transitioned towards sustainable practices, offer a diverse palette of innovative strategies. They encompass distinctive sustainable practices ranging from upcycling, promoting second-hand fashion, adhering to sustainable production methodologies, to the use of recycled fabrics. Utilizing qualitative methodologies, this research adopted a comparative approach, interviewing 12 such distinctive brands alongside a consultant specializing in second-hand fashion. This method depicted a rich, multifaceted perspective on the challenges intrinsic to circular business models in the fashion domain. From this exploration, the findings were clustered into three predominant categories: striking a balance between economic viability, ecological responsibility, and social equity; identifying and leveraging driving factors while recognizing potential opportunities; and understanding and navigating barriers that hinder circular adoption. This study stands as an important contribution to existing literature, providing a nuanced roadmap specifically tailored for French micro and small-sized brands. Its insights illuminate pathways, guiding these brands towards the successful adoption and nuanced implementation of circular business models among a challenging industry context.